1983
DOI: 10.1159/000115658
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological Effects of Pentoxifylline on Disturbed Flow Behavior of Blood in Patients with Cerebrovascular Insufficiency

Abstract: The influence of pentoxifylline (11–18 mg/kg orally, Trental 400) on impaired hemorheologic conditions has been investigated in a total of 73 patients with CVI. Throughout a treatment period of 4 weeks, there was a significant improvement in red cell behavior and a significant inhibition of increased platelet aggregation; moreover, a fall in plasma fibrinogen and of blood viscosity has also been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The decrease in plasma fibrinogen by ticlopidine [16] is paralleled by changes in leukocyte counts. In keeping with an inhibitory effect on plasma fibrinogen [17][18][19][20][21][22], pentoxifylline, a phosphodiesterase inhibitor, is known to increase intracellular levels of cAMP. Protein kinase C is involved in the regulation of plasma fibrinogen [7].…”
Section: Factors Affecting Plasma Fibrinogen Levelsmentioning
confidence: 99%
“…The decrease in plasma fibrinogen by ticlopidine [16] is paralleled by changes in leukocyte counts. In keeping with an inhibitory effect on plasma fibrinogen [17][18][19][20][21][22], pentoxifylline, a phosphodiesterase inhibitor, is known to increase intracellular levels of cAMP. Protein kinase C is involved in the regulation of plasma fibrinogen [7].…”
Section: Factors Affecting Plasma Fibrinogen Levelsmentioning
confidence: 99%
“…Other therapeutic approaches seek to limit cerebral infarction by slowing cerebral metabolism, 1 controlling perifocal brain edema, 2 or enhancing collateral blood flow to the peri-infarct region. This is attempted by treatment with vasodilatation, 3 drugs that influence erythrocyte deformability, 4 or hemodilution. Hematocrit is the main determinant of whole-blood viscosity.…”
mentioning
confidence: 99%
“…26 Several clinical studies have suggested a potential therapeutic or prophylactic efficacy of PTX in ischemic cerebrovascular disorders. 27 " 32 Our study was designed to assess the efficacy and safety of PTX on the survival, neurologic deficits, and extent of recovery after acute nonhemorrhagic stroke using a randomized, placebocontrolled, double-blind protocol.…”
mentioning
confidence: 99%